Free radical scavenging activity of Kielmeyera variabilis (Clusiaceae) - Coqueiro, Aline [UNESP]; Regasini, Luis Octávio [UNESP]; Skrzek, Scheila Cristina Gutkoski [UNESP]; Queiroz, Marcos Marçal Ferreira [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (MDPI, 2013)
As part of our ongoing research on antioxidant agents from Brazilian flora, we screened the free radical scavenging activity of two extracts and eight fractions of Kielmeyera variabilis (Clusiaceae) using DPPH (2,2-diphenyl-1- picrylhydrazyl-hydrate) and ABTS+ [2,2'-azinobis(3- ethylenebenzothiazoline-6-sulfonic acid)] colorimetric assays. The ethyl acetate and n-butanol fractions of the leaves of K. variabilis displayed the strongest activity (IC50 of 3.5 ± 0.3 and 4.4 ± 0.2 μg mL -1 for DPPH and 6.6 ± 0.4 and 3.1 ± 0.1 μg mL -1 for ABTS+, respectively). Chromatographic fractionation of the most potent fractions led to identification of three flavonols with previously described antioxidant activity, quercitrin (1), quercetin-3-O- glucoside (3), and quercetin-3-O-galactoside (4), and of one biflavone, podocarpusflavone A (2). This is the first time that the presence of these flavonoids in Kielmeyera variabilis has been reported. © 2013 by the authors.
Keywords: ABTS+; Antioxidant; Clusiaceae; DPPH; Flavonoid; Flavonol; Free radical scavenging activity; Kielmeyera variabilis; 1,1 diphenyl 2 picrylhydrazyl; 2,2' azino di (3 ethylbenzothiazoline) 6 sulfonic acid; 2,2'-azino-di-(3-ethylbenzothiazoline)-6-sulfonic acid; 2,2-diphenyl-1-picrylhydrazyl; benzothiazole derivative; biphenyl derivative; flavonoid; picric acid; scavenger; sulfonic acid derivative; chemistry; IC 50; metabolism; Benzothiazoles; Biphenyl Compounds; Flavonoids; Free Radical Scavengers; Inhibitory Concentration 50; Picrates; Sulfonic Acids